2021
DOI: 10.1080/16506073.2021.1952302
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of randomised controlled trials of cognitive behaviour therapy for perfectionism: a systematic review and meta-analysis

Abstract: Perfectionism is a transdiagnostic process across anxiety, depression, and eating disorders.The aim of this systematic review was to examine the efficacy of self-help and face to face CBT for perfectionism in reducing perfectionism and anxiety, depression, and eating disorders. A total of 15 randomised controlled trials of CBT for perfectionism were identified (N = 912 participants; mean pooled age = 23 years) which met inclusion criteria. There were medium or large effect sizes found on perfectionism measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 44 publications
(59 reference statements)
2
56
2
5
Order By: Relevance
“…The FMPS is a well-validated measure of perfectionism that contains 35 questions across six subscales; Concern Over Mistakes, Doubts About Actions, Personal Standards, Parental Expectations, Organization, and Parental Criticism ( Frost et al, 1990 ). In this study only the 9-item concern over mistakes (CM; negative reactions to mistakes) and 7-item personal standards (PS; setting high standards) will be used as an additional outcome measure of perfectionism as these scales are the most clinically relevant subscales of the measure ( Shafran et al, 2002 ) and widely used as outcomes measures in RCTs of CBT-P ( Galloway et al, 2022 ). The FMPS has excellent internal consistency (α = 0.90) ( Frost et al, 1990 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FMPS is a well-validated measure of perfectionism that contains 35 questions across six subscales; Concern Over Mistakes, Doubts About Actions, Personal Standards, Parental Expectations, Organization, and Parental Criticism ( Frost et al, 1990 ). In this study only the 9-item concern over mistakes (CM; negative reactions to mistakes) and 7-item personal standards (PS; setting high standards) will be used as an additional outcome measure of perfectionism as these scales are the most clinically relevant subscales of the measure ( Shafran et al, 2002 ) and widely used as outcomes measures in RCTs of CBT-P ( Galloway et al, 2022 ). The FMPS has excellent internal consistency (α = 0.90) ( Frost et al, 1990 ).…”
Section: Methodsmentioning
confidence: 99%
“…Perfectionism is a risk and perpetuating factor for eating disorder symptoms in adults ( Fairburn et al, 2003b ; Limburg et al, 2017 ) and adolescents ( Johnston et al, 2018 ; Vacca et al, 2021 ). Cognitive behaviour therapy for perfectionism (CBT-P) has been demonstrated in recent meta-analyses to have medium effects on eating disorder symptoms ( g = 0.61 ( Galloway et al, 2022 ); g = 0.64 ( Robinson and Wade, 2021 )) and transdiagnostic impacts on anxiety ( g = 0.42) and depressive ( g = 0.60) symptoms ( Galloway et al, 2022 ). Numerous studies have demonstrated the efficacy of CBT-P on reducing perfectionism and psychopathology, delivered via the internet in unguided (e.g., Egan et al, 2014 ; Grieve et al, 2022 ; Shu et al, 2019 ; Valentine et al, 2018 ; Wade et al, 2019 ) and guided formats ( Rozental et al, 2017 ; Shafran et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, understanding its detrimental health consequences has become an increasingly relevant concern (e.g., Limburg et al, 2017; Smith et al, 2021). Third, interventions exist that reduce perfectionism (for meta‐analyses see Galloway et al, 2021; Lloyd et al, 2015). Thus, perfectionism may be a modifiable risk factor for sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…The present study aimed to translate the CPQ into Arabic and to examine its psychometric properties using the Rasch methodology, a robust statistical approach increasingly becoming a gold standard in rehabilitation medicine [ 36 ]. The CPQ was chosen over the other multidimensional measures due to its appropriate fit within the cognitive-behavioral therapy model, which is considered the gold standard for treating clinical perfectionism [ 14 ].…”
Section: Introductionmentioning
confidence: 99%